Social Network Analysis on Youtube Comments: A Case Study of the 2024 Presidential Candidate Debate (December 12, 2023) Metro TV) - Putri Shalsa Bil Balqis (Green Publisher Indonesia, 2025)
This research aims to find out how to analyze social networks on YouTube comments in the case study of the 2024 Presidential Candidate Debate (12 December 2023) Metro TV. This research uses Social Network Analysis (SNA) analysis on YouTube social media. This research uses a qualitative method with a case study approach to look at the phenomenon in depth. The population in this study are account users who provided comments on Metro TV's 2024 Presidential Candidate Debate (12 December 2023) broadcast. The results of the analysis via Gephi showed that the highest degree centrality was found on the account @abdurrahmanmisbah1531. Meanwhile betweenness centrality on the @DahmanHarahap-ot5yx account. And finally, closeness centrality, there are 984 actors who have closeness to other actors.